2018
DOI: 10.1148/radiol.2018170803
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds: Imaging and Clinical Significance

Abstract: Cerebral microbleeds (CMBs), also referred to as microhemorrhages, appear on magnetic resonance (MR) images as hypointense foci notably at T2*-weighted or susceptibility-weighted (SW) imaging. CMBs are detected with increasing frequency because of the more widespread use of high magnetic field strength and of newer dedicated MR imaging techniques such as three-dimensional gradient-echo T2*-weighted and SW imaging. The imaging appearance of CMBs is mainly because of changes in local magnetic susceptibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
174
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(184 citation statements)
references
References 103 publications
6
174
1
3
Order By: Relevance
“…8 As expected, MBs were more easily detected with higher magnetic strength and SWI. 9 The distribution and extent of microbleeds we describe may be distinct for severe HACE. Microbleeds reported in other conditions are usually far fewer in number, in different distributions, and lack the fine black pepper appearance.…”
Section: Microbleedsmentioning
confidence: 75%
See 1 more Smart Citation
“…8 As expected, MBs were more easily detected with higher magnetic strength and SWI. 9 The distribution and extent of microbleeds we describe may be distinct for severe HACE. Microbleeds reported in other conditions are usually far fewer in number, in different distributions, and lack the fine black pepper appearance.…”
Section: Microbleedsmentioning
confidence: 75%
“…Microbleeds reported in other conditions are usually far fewer in number, in different distributions, and lack the fine black pepper appearance. 9 Previous studies using SWI in subjects after high altitude exposure support this view. Eleven of 13 climbers with a history of HACE demonstrated residual MBs, with only severe cases or those with HAPE showing the extensive distribution similar to that in our patients.…”
Section: Microbleedsmentioning
confidence: 88%
“…The detection rate of cortical microinfarcts was also improved considerably by imaging at 7 T in comparison to 3 T, which was confirmed histologically through subsequent serial sectioning. Therefore, technical limitations, such as field strength, image resolution, pulsesequence parameters and MRI-histological matching were considered to be the major sources for obtaining false negative results [15,25,47,49]. However, our analyses with a field strength of 11.7 T now showed that there is also some variability in the histopathological features of cortical cerebral microinfarcts, including not only their size and shape, the cortical layer in which they occur, thinning, and cavitation, but also the degree of iron accumulation, which influenced MRI signals and the detectability of microinfarcts in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture or occlusion of these arterioles could be caused by CAA or atherosclerosis of leptomeningeal vessels and their arteriolar branches that supply the cerebral cortex [31,43]. Other causes of cortical cerebral microinfarcts include thrombotic microembolisms originating from the heart (e.g., endocarditis) or plaques in cerebral arteries, lipid microembolisms following major surgeries, hereditary forms of small vessel disease such as CADASIL, leukoencephalopathy, and radiation therapy [11,25].…”
Section: Discussionmentioning
confidence: 99%
“…Today, in radiological routine, physiological ageing assessment consists in mostly 4 tasks, such as (i) categorical assessment of atrophy (eg : medial temporal lobe atrophy score (MTA), aiming to distinguish normal to pathologic atrophy (Gaillard s. d.)), (ii) assessment of ventricles dilatation (the task consists in identifying atrophy to hydrocephalus), (iii) assessment of White Matter Hyperintensities (WMH) on MRI T2 sequences (this tasks consists in firstly identifying the leukoaraiosis pattern vs other WHM patterns (for eg : inflammatory, such as in multiple sclerosis), and secondly grading level of leukoaraiosis with Fazekas scale (Fazekas et al 1987)), and (iv) detect, count, and assess spatial distribution of cerebral microbleeds (CMBs), in order to distinct normal ageing in the brain to the main differential diagnostics : high cardiovascular risk (deep spatial repartition CMBs are associated with small vessel disease due to hypertension) versus Amyloid angiopathy (superficial, lobar distribution of CMBs) ; for a recent review see (Haller et al 2018). Schematically, 3 MRI sequences are used for this 4 tasks : T1 weighted MRI for grey matter and CSF, T2 weighted (FLAIR sequence) for white matter (and CSF), T2* or SW for CMBs assessments.…”
Section: Brain Ageing In Radiologymentioning
confidence: 99%